Effect of corticosteroids on sperm antibody concentration in different biological fluids and on pregnancy outcome in immunologic infertility - Ulcova-Gallová, Z; Bouse, V; Rokyta, Z; Krizanovská, K (Zentralblatt fur Gynakologie, 2000)
OBJECTIVE: In the last fourteen years, detection of free spermagglutinating antibodies has been performed by tray agglutination test (TAT) and by direct/indirect mixed antiglobulin reaction test (MAR) in 696 infertile couples aged 23-42 years (female) and 26-52 years (male) with previously undiagnosed infertility. MATERIAL AND METHODS: Oral decreasing doses of prednisone or dexamethasone for three months in the case of serum or seminal plasma spermantibodies, plasmapheresis in one patient with serum spermantibodies were used. Hydrocortisone to the ectocervix was applicated in patients with spermagglutinating antibodies in cervical ovulatory mucus. RESULTS: Serum IgG spermagglutinating antibodies totally disappeared in 3 out of 11 men, and four out of 15 women. But serum IgM sperm antibodies persisted. One female patient was treated with corticosteroids and also with plasmapheresis. Seminal plasma IgG spermagglutinating antibodies were greatly influenced in 57.8% of the patients, IgA in 38.9% and each case by oral corticosteroids. A decrease of IgG and IgA spermagglutinating antibodies in ovulatory cervical mucus during hydrocortisone local application was registered in 61.3%, IgG in 50.7% and IgA in 65.9%. Levels of IgM spermagglutinating antibodies in cervical ovulatory mucus were not influenced, spermantibodies in IgA and IgE were affected very little. CONCLUSION: The corticosteroid influence of immunocompetent cells in each case must be chosen individually with regard to the localisation of spermantibodies. We often combine the long lasting corticosteroids treatment with in vitro fertilization. The therapy seems to be very promising for the improvement of immunological causes of infertility.
Keywords: Semen; Infertility, Male; prednison; těhotenství; ženská infertilita; lidé; výsledek terapie; Glucocorticoids; imunologické testy; výsledek těhotenství; Middle Aged; mužské pohlaví; aplikace orální; glukokortikoidy; Adult; Cervix Mucus; Infertility, Female; cervikální hlen; ženské pohlaví; Humans; sperma; Prednisone; Pregnancy; dexamethason; Pregnancy Outcome; autoprotilátky; lidé středního věku; Administration, Oral; mužská infertilita; Dexamethasone; Immunologic Tests; dospělí; Female; Spermatozoa; Treatment Outcome; Autoantibodies; spermie; Male